Phylogeny of Indo-West Pacific pontoniine shrimps (Crustacea: Decapoda: Caridea) based on multilocus analysis - Gan, Zhi Bin; Li, Xin Zheng; Chan, Tin-Yam; Chu, Ka Hou; Kou, Qi (Journal of zoological systematics and evolutionary research, 2015)
The phylogenetic relationships and evolutionary processes within the subfamily Pontoniinae, a speciose group of shrimps with diverse lifestyles (free living, semi‐symbiotic and symbiotic) inhabiting the coral reefs of tropical oceans, are an interesting and undeveloped subject of study. In this work, two mitochondrial ribosomal genes (12S rRNA and 16S rRNA) and two protein‐coding nuclear genes (Histone 3 and the sodium–potassium ATPase α‐subunit) were employed to reconstruct the phylogenetic relationships of 42 genera and 101 species within Pontoniinae. Compared to previous studies, ten additional genera were shown to be monophyletic groups, and the genera Dactylonia and Periclimenaeus were shown to be paraphyletic. The shallow‐water crinoid‐associated pontoniines were divided into several groups which were mostly consistent with the morphological analysis. The studied bivalve‐associated taxa exhibited ancestries that were traceable to different lineages, and two groups could be distinguished: Anchiopontonia + Conchodytes and Anchistus. The similar situation occurred in other echinoderm‐associated pontoniines. These results suggest that pontoniines sharing the same hosts may have different evolutionary origins resulting from multiple intrusions of their hosts by morphologically plastic ancestral groups. The phylogenetic relationships of the subfamily Pontoniinae was discussed based on mitochondrial and nuclear DNA. Among the 20 genera with more than one species included in the analysis, monophyly was evident with strong nodal support for 16. The genera Periclimenaeus and Dactylonia were shown to be paraphyletic. The results suggest that pontoniines sharing the same hosts may have different evolutionary origins resulting from parallel intrusions of their hosts by morphologically plastic ancestral groups.